A novel drying system – simultaneous use of ohmic heating with convectional air drying: System design and detailed examination using CFD. (August 2021) - Turgut, Sebahattin Serhat; Küçüköner, Erdoğan; Feyissa, Aberham Hailu; Karacabey, Erkan
Abstract: This paper introduces a novel drying system called ohmic assisted drying ( OAD ) – the simultaneous combination of ohmic heating and convectional air drying. The OAD system improved the drying characteristics of potato slices. Depending on the process conditions, drying time was shortened by 20–60% by OAD compared to conventional air-drying system. The level of applied voltage and air temperature were effective on drying time reduction. To achieve a better understanding of the changes in potato slices during OAD, a 3D mechanistic model was developed and validated with experimental moisture and temperature results. The model involves coupled heat, mass, momentum transfer as well as heat generation due to electrical current through the porous media. A non-conjugate, macroscopic, non-equilibrium modelling approach helps to define OAD process. Drying material (potato) consists of solid matrix, water, and gas phases, where pressure-driven flow, binary diffusion and phase change in drying volume were considered. The model predicts the spatial distribution of temperature, moisture, and pressure in the drying material. The prediction performance of the model is satisfactory especially in terms of moisture content since the standard error of estimate changes between 0.05 and 0.23. A deeper understanding is presented about the mechanisms of OAD highlighting strengths and weaknesses of the model and the drying system. Highlights: A novel drying method, namely simultaneous use of ohmic heating with convectional drying, is introduced. Ohmic heating can accelerate drying by 20–60%, when combined with convective heating. A CFD model consisting of heat, mass, momentum transfer with electric current was developed for drying of porous materials. The model can predict moisture and temperature changes during drying. A good agreement between the experimental and predicted results were obtained.